Analisis Pendapatan Usahatani Cabai Merah Di Desa Kamanga Dua Kecamatan Tompaso Kabupaten Minahasa - Sumampow, Militia Christi; Manginsela , Elsje Pauline; Talumingan, Celcius (AGRI-SOSIOEKONOMI, 2023)
The study aimed to determine the income of red chili farming in Kamanga Dua Village, Tompaso District, Minahasa Regency. The research was conducted in August 2023. This research uses 2 types of data, namely primary and secondary data. Primary data were obtained from direct interviews using a list of questions as a tool in data collection. Secondary data were obtained from literature related to the research. Sampling in this study used purposive sampling technique.  The number of research samples was 5 farmers as respondents. The results of the study were analyzed using farm analysis, namely cost analysis, revenue, income and continued with the Revenue Cost Ratio. The results of this study indicate that the average income obtained in red chili farming in Kamanga Dua Village, Tompaso District, Minahasa Regency is IDR 44,039,222 per one growing season obtained from the average receipt of IDR 65,798,000 and the average total cost of IDR 21,758,778. The income obtained from red chili farming in one month amounted to Rp14,679,741 which was obtained from the income divided by three months of harvest. The R/C Ratio analysis shows that red chili farming in Kamanga Dua Village, Tompaso District, Minahasa Regency is feasible. This is seen from the ratio of total income to total costs which is> 1, namely 3.02.